Becoming a manager : how new managers master the challenges of leadership - Hill, Linda A. 1956- (Harvard Business Press, 2003)
"In tracing and analyzing the experiences of nineteen new managers, Linda Hill reveals the profound complexity and difficulty of the process of developing into a manager. In their own distinct voices, these managers describe how they reframed their understanding of their roles and responsibilities and how they coped with the stresses and emotions of the transformation - in essence, how they were able to take on a new identity. Now, in an expanded second edition, the author offers concrete advice on the crucial issues of dealing effectively with organizational politics and developing and leading diverse teams in times of change, as well as on how managers can prepare themselves to lead over the course of their careers. In a new epilogue, she explores what organizations can do to help managers in their journey to lead and learn."--Jacket.